2014
DOI: 10.1136/archdischild-2013-305892
|View full text |Cite
|
Sign up to set email alerts
|

Is synchronised NIPPV more effective than NIPPV and NCPAP in treating apnoea of prematurity (AOP)? A randomised cross-over trial

Abstract: Background Apnoea, desaturations and bradycardias are common problems in preterm infants which can be treated with nasal continuous positive airway pressure (NCPAP) and nasal intermittent positive pressure ventilation (NIPPV). It is unclear whether synchronised NIPPV (SNIPPV) would be even more effective. Objective To assess the effects of flow-SNIPPV, NIPPV and NCPAP on the rate of desaturations and bradycardias in preterm infants and, secondarily, to evaluate their influence on pattern of breathing and gas e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
66
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 95 publications
(69 citation statements)
references
References 37 publications
2
66
1
Order By: Relevance
“…Our clinical observations [14,29,31] are consistent with laboratory data [16] and show that the Giulia® flow-trigger is reliable to provide SNIPPV for treatment of neonatal respiratory failure. From clinical trials, SNIPPV seems more effective than NIPPV and NCPAP in reducing need for intubation in RDS, in improving the success of extubation and in treating apnea of prematurity, with a reassuring absence of relevant side effects.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Our clinical observations [14,29,31] are consistent with laboratory data [16] and show that the Giulia® flow-trigger is reliable to provide SNIPPV for treatment of neonatal respiratory failure. From clinical trials, SNIPPV seems more effective than NIPPV and NCPAP in reducing need for intubation in RDS, in improving the success of extubation and in treating apnea of prematurity, with a reassuring absence of relevant side effects.…”
Section: Discussionsupporting
confidence: 77%
“…As it is unclear whether SNIPPV would be even more effective in treating apnea, we conducted a clinical trial to assess the effects of NCPAP, NIPPV and flow-SNIPPV on rates of desaturations and bradycardias in VLBW infants and to evaluate the influence of these modes of ventilation on pattern of breathing and gas exchange [31]. Nineteen infants with a mean gestation at study of 30 weeks suffering from apneic spells were enrolled in a randomized controlled trial with a cross-over design.…”
Section: Clinical Results With Snippvmentioning
confidence: 99%
“…Recently, a group in Italy published a randomised, crossover study of synchronised non-invasive positive pressure ventilation (S-NIPPV) compared with standard NIPPV or CPAP in 19 preterm infants that found S-NIPPV to be more effective in reducing central apnoea 35. This new respiratory modality should be studied in a larger cohort to see whether the benefit is reproducible.…”
Section: Treatmentmentioning
confidence: 99%
“…Gizzi et al [17] recently reported that flow-synchronized nasal intermittent positive pressure ventilation (i.e. S-NIMV), compared to NIMV or CPAP, is associated with less desaturation and/or bradycardia and central apnea in preterm infants.…”
Section: Discussionmentioning
confidence: 99%
“…Our study demonstrated that during S-NIMV, 10 infants had no severe bradycardia events but that during NIMV, only 5 infants had no such events. Flow synchronization for NIMV is only available with the specific ventilator used by Gizzi et al [17] , which seems to be able to synchronize despite large leaks which usually occur with noninvasive ventilation in neonates. Other studies demonstrated that asynchronous ventilator inflations might increase the risk of adverse effects like pneumothorax [13] , BP and cerebral blood flow velocity fluctuations [8,18] as well as WOB in immature infants [8,10] .…”
Section: Discussionmentioning
confidence: 99%